2022
DOI: 10.1038/s41598-022-13009-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of gut microbiota during the first 2 years of life

Abstract: Although development of microbiota in childhood has been linked to chronic immune-related conditions, early childhood determinants of microbiota development have not been fully elucidated. We used 16S rRNA sequencing to analyse faecal and saliva samples from 83 children at four time-points during their first 2 years of life and from their mothers. Our findings confirm that gut microbiota in infants have low diversity and highlight that some properties are shared with the oral microbiota, although inter-individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…This is in line with previous reports indicating significant changes in the dominant phyla and diversity appearing from age 3 months onwards 16 or at the end of the first year of life 41 until the parent’s diversity and composition is reached by month 14 16 or on the second birthday. 42 None of the three types of supplementation investigated in this study were able to fully recreate the breast milk-related microbial environment. Accordingly, the fecal metabolic profile of 3-months old, breast-fed babies was clearly distinguishable from formula-consuming infants.…”
Section: Discussionmentioning
confidence: 86%
“…This is in line with previous reports indicating significant changes in the dominant phyla and diversity appearing from age 3 months onwards 16 or at the end of the first year of life 41 until the parent’s diversity and composition is reached by month 14 16 or on the second birthday. 42 None of the three types of supplementation investigated in this study were able to fully recreate the breast milk-related microbial environment. Accordingly, the fecal metabolic profile of 3-months old, breast-fed babies was clearly distinguishable from formula-consuming infants.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, we observed high Prevotella levels at baseline which increased signi cantly at later time points 9 and 12 months. The age group of the participants in this study was restricted to 11-15 years, this is important to note considering the variability associated with the microbiome structure of kids as they grow 42,56,57 . Our selection of this age group is based on our previous work, where we have demonstrated that there were no age-speci c effects on the gut microbiome 13 .…”
Section: Discussionmentioning
confidence: 99%
“…There are three pivotal stages in the development of the gut microbiome: birth, adolescence, and old-age ( 15 ). Substantial changes occur in human gut microbiota during the first two years of life, as the gut microbiota of neonates shifts during development to be more similar to adult microbiota by 24 months of age ( 37 ) and is continuing to increase in communal diversity by five years of age ( 38 ). Gut microbiome diversity appears to be relatively constant from adolescence through adulthood; however, alterations in the microbiome have been observed between the 60–80 year-old- and >80 year-old-individuals ( 32 ).…”
Section: The Aging Microbiomementioning
confidence: 99%